Awards at work - Susanne Neckermann; Reto Cueni; Bruno S. Frey (Center for Research in Economics, Management and the Arts (CREMA), 2010)
Awards - widespread in the corporate sector and elsewhere - are motivators that derive their value from non-pecuniary concerns such as status and self-image. Quasi-experimental panel data from the call center of a large international bank allow us to estimate the causal impact on effort when receiving an award. The performance of winners proves to be significantly higher than that of comparable nonrecipients after the award has been presented. This increase in work effort is sizeable and robust. We investigate the various theories that could explain the change in behavior. We find that image concerns most likely drive the effect.
Keywords: C23; J33; M52; 330; Awards; Motivation; Non-monetary Compensation; Insider Econometrics